POTRET PEMBELAJARAN DARING MATAKULIAH KAJIAN KEBAHASAAN DI PGSD FIP UNIMED - Faisal Faisal (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
The purpose of this study is to describe the implementation of online learning for the even semester 2020/2021 Language Studies course in the PGSD FIP UNIMED study program. This research is a qualitative descriptive study. The population used in this study were all second semester students who took the Language Studies course at the PGSD FIP UNIMED Study Program. Samples were taken involving 187 respondents. The instrument used in the study was an online questionnaire with a google form. The data analysis technique was carried out by qualitative analysis with 4 stages of activities, including: data collection, data reduction, data presentation, and drawing conclusions. The results showed: (1) the average score of the teaching and learning process is 4.11 (Good), (2) the average score of capability/competence of lecturers is 4.28 (Good), (3) the average score of supporting facilities and infrastructure is 3 ,93 (Good), and (4) the most dominant challenge is the need to improve IT skills and effectiveness in time management.Keywords: online learning, language studies, PGSD.